The presumption of dangerousness in sexually violent predator commitment proceedings. (11th January 2014) - Scurich, Nicholas; Krauss, Daniel A.
Abstract : Twenty states, the District of Columbia, and the federal government have adopted sexually violent predator (SVP) Laws, which permit the post-incarceration confinement of persons who: (1) have a previous conviction or charge for a sexual offence; (2) suffer from a mental abnormality; and (3) are likely to engage in future acts of sexual aggression. Although most who are convicted of a sexual offence will not be subject to SVP commitment, a burgeoning body of research indicates that commitment is highly likely once the decision is placed in the hands of the jury. The high rate of commitment suggests that there might be a presumption of dangerousness in these proceedings, possibly stemming from the previous conviction requirement. This potential explanation was tested in the current experiment. Jury-eligible participants ( n = 190) were provided with varying degrees of information pertaining to the SVP commitment criteria. Some participants were told only that a person had been referred for an SVP commitment proceeding, whereas others were given information relevant to some or all three of the legal criteria. The rate of commitment did not vary as a function of the information provided. The mere fact that a respondent had been referred for an SVP proceeding was sufficient for a majority of participants to authorize commitment. We then calculated participants' implicit operationalization of the 'likely to offend' criterion. On average, participants require the risk of recidivism to exceed 31% (range 20–40%) to effectuate commitment. These findings raise concerns about whether the constitutionally required due process occurs in SVP commitment proceedings.